Adherence, knowledge, and perception about oral anticoagulants in patients with atrial fibrillation at high risk for thromboembolic events after radiofrequency ablation. (30th August 2018) - Smet, Lily; Heggermont, Ward A.; Goossens, Eva; Eeckloo, Kristof; Vander Stichele, Robert; De Potter, Tom; De Backer, Tine
Abstract: Aims: This study aimed to: (a) determine adherence rates to oral anticoagulants in atrial fibrillation patients with a high risk for thromboembolic events postradiofrequency ablation; (b) evaluate patients' knowledge and perceptions towards oral anticoagulants; and (c) explore the impact of patients' knowledge and perceptions on treatment adherence. Background: Atrial fibrillation is a common arrhythmia associated with an increased risk of developing thromboembolic events such as stroke. Although adherence to oral anticoagulants is crucial to prevent such complications, the relationship between adherence, knowledge and patient perceptions is poorly understood in patients with atrial fibrillation at high risk for thromboembolic events after radiofrequency ablation. Design: A cross‐sectional observational survey study was performed in a single centre. Methods: The levels of adherence, knowledge, and perception towards oral anticoagulants were assessed using the 8‐item Morisky Medication Adherence Scale, Knowledge of Oral Anticoagulation Tool, Perception of Anticoagulant Treatment Questionnaire and Benefit‐Risk Perception Tool, respectively. Results from these self‐reported tools were analysed descriptively. A multivariable binary logistic regression model was used to identify factors associated with levels of adequate adherence. Results: Adequate treatment adherence was found in three‐quarters of patients. The total mean knowledge score was low. Participants expressed high ease of use and low burden of treatment. Higher total knowledge and satisfaction scores were significant factors associated with higher levels of adherence. Conclusion: There remains a huge unmet need to follow‐up and educate patients with atrial fibrillation, focusing on good knowledge and correct perception of the advantages and disadvantages of oral anticoagulants. Our results suggest that increased knowledge and satisfaction rates might have a positive impact on adherence to oral anticoagulants. Abstract : 目标: 本研究旨在:(a)确定在射频消融术后易患血栓的房颤患者口服抗凝血剂的依从率;(b)评估患者对口服抗凝血剂的了解和认知;以及(c)探讨患者的了解和认知对治疗依从性的影响。 背景: 房颤是一种常见的心律失常, 与中风等患血栓的风险增加有关。尽管坚持口服抗凝血剂对于预防这种并发症非常重要, 但对射频消融术后易患血栓的房颤患者的依从性、了解和患者认知之间的关系却知之甚少。 设计: 进行了单中心横断面观察性调查研究。 方法: 对口服抗凝血剂的依从性、了解和认识水平进行了评估, 分别采用了8条目Morisky服药依从性量表、口服抗凝治疗工具知识、抗凝治疗问卷的看法和利弊认知工具。对这些自我报告工具的结果进行了描述性分析。同时, 采用了多变量二元逻辑回归模型来确定与适当依从性水平相关的因素。 结果: 在四分之三的患者中发现有适当的治疗依从性。总平均了解评分较低。受试者表现出了对治疗的高度接受和较低的心理负担。此外, 较高的了解和满意度总分是与更高的依从性水平相关的重要因素。 结论: 仍有大量未被满足的需求, 需要对房颤患者进行随访和教育, 以便患者良好了解和正确认识口服抗凝血剂的优缺点。研究结果表明, 增加的了解和满意度可能对口服抗凝血剂的依从性有积极的影响。